Achilles tendon rupture: physiotherapy and endoscopy-assisted surgical treatment of a common sports injury - Mahmut Nedim Doral; Murat Bozkurt; Egemen Turhan; et al (Dove Medical Press, 2010)
Mahmut Nedim Doral1,2, Murat Bozkurt3, Egemen Turhan4, Gürhan Dönmez2, Murat Demirel5, Defne Kaya2, Kivanç Atesok7, Özgür Ahmet Atay1, Nicola Maffulli61Department of Orthopedics and Traumatology, 2Department of Sports Medicine, Hacettepe University School of Medicine, Sihhiye, Ankara, Turkey; 3Department of Orthopedics and Traumatology, Ankara Etlik Ihtisas Training and Research Hospital, Ankara, Turkey; 4Department of Orthopedics and Traumatology, Zonguldak Karaelmas University School of Medicine, Zonguldak, Turkey; 5Department of Orthopedics and Traumatology, Ankara Bayindir Medical Center, Ankara, Turkey; 6Centre for Sports and Exercise Medicine, Barts and The London School of Medicine and Dentistry, Queen Mary University of London, London, UK; 7St. Michael's Hospital Division of Orthopaedics Musculoskeletal Research Lab, Toronto, Ontario, CanadaAbstract: Although the Achilles tendon (AT) is the strongest tendon in the human body, rupture of this tendon is one of the most common sports injuries in the athletic population. Despite numerous nonoperative and operative methods that have been described, there is no universal agreement about the optimal management strategy of acute total AT ruptures. The management of AT ruptures should aim to minimize the morbidity of the injury, optimize rapid return to full function, and prevent complications. Since endoscopy-assisted percutaneous AT repair allows direct visualization of the synovia and protects the paratenon that is important in biological healing of the AT, this technique becomes a reasonable treatment option in AT ruptures. Furthermore, Achilles tendoscopy technique may decrease the complications about the sural nerve. Also, early functional postoperative physiotherapy following surgery may improve the surgical outcomes.Keywords: Achilles tendon rupture, percutaneous repair, endoscopic control, growth factors